Incidence of Soil Transmitted Helminth (STH) Infection in School-Age Children in the Archipelago of North Sulawesi - Lalangpuling, Indra Elisabet; Bawataa, Janiver; Sumenge, Dionysius; Sumampou, Jonas (Jurnal Analis Medika Biosains (JAMBS), 2022)
Archipelagic areas are areas that are still lacking in the application of good sanitation life. One of the infectious diseases related to sanitation is worm infection. This study aims to identify the presence or absence of Soil Transmitted Helminth (STH) intestinal parasitic infection in children in the archipelago. This research was carried out at the Bethel Alo Christian Education Foundation Elementary School, Talaud Regency. This research is a descriptive research. The sampling technique is Porposive sampling, the sample of this research is 35 samples. After microscopic examination using faecal samples, it was found that 5 samples were positive for helminthiasis while 30 other samples were negative. Of the 5 samples, 2 positive samples of Ascaris lumbricoides worm eggs, 2 samples of Trichuris trichiura, and 1 sample of mixed infection of Ascaris lumbricoides and Trichuris trichiura. The results showed as many as 5 positive samples or 14.29% of the 35 samples consisting of 2 samples or 5.71% of Ascaris lumbricoides, 5.71% of Trichuris trichiura, and 1 sample of Mix infection or 2.85%.